Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content:1. Awareness and practices of king Khalid university students in virtual clothingDr. Amani Shaaban Ali Mohamed2. The feasibility of the Palestinian movement to implement boycott systems for a state of Zionist occupation: a reading of the results, challenges, and the future of the movementMr. Mohammad A. Jaradat3. The role of national platforms in charitable work (Ehsan platform as a model) Society of the Kingdom of Saudi ArabiaMrs. Bashaier Abdullah Al-Zahrani4. An Analysis of Visual Metaphor to Understand Creativity in Contemporary ArtDr. Rihab Abdullah Alghathami5. Mechanisms of digital technology in establishing the quality of scientific researchMrs. Lallouche Samira6. The Implications of Covid-19 on Increased Social Distancing for At-Risk Youth in Israel's Arab CommunityDr. Rodayna Kamal Badir, Dr. Anan Abu-Saleh , Dr. Omar Abd -Alrahim Nasrallah7. The Constructive Contexts of the Artistic Profile of Nations and populationsDr. Fouzia Bouchareb
Keywords: Journal of Human and Social Sciences